Verrucous haemangioma - Chand M; Gangopadhya DN; Chakravarty K; Pal D (Wolters Kluwer Medknow Publications, 1996)
ABSTRACT: A 15 year old boy presented with a verrucous plaque on left leg above the ankle. There was history of bleeding on trauma on several occasion. The lesion was present at birth as an erythematous macule. Histopathological examination established the diagnosis of verrucous haemangioma. Surgical excision has been done.